Active Thermal Control for Power Semiconductor using Peltier-Device - Yamaguchi, Masamichi; Watanabe, Hiroki; Itoh, Jun Ichi; Lee, Kyo Beum (2024 IEEE Energy Conversion Congress and Exposition, ECCE 2024 - Proceedings, 2024)
The paper proposes an Active Thermal Control (ATC) approach employing a Peltier device as a heat exchanger for temperature regulation. The control strategy relies on Model Predictive Control (MPC) utilizing an equivalent thermal model. It elucidates the current control methodology for the Peltier device based on this model and predicted temperature. Moreover, the predicted temperature and additional thermal sensor estimate the loss amount at the heat source without any electrical sensor, such as a current or a voltage sensor. The simulation result affirms the effectiveness of the proposed control and loss estimation method. Finally, the experimental result demonstrates the validity of the proposed control, evidenced by a 2.6% maximum error in temperature control.
Keywords: current; Active thermal control; Control approach; Control strategies; Model predictive control; Model-predictive control; Peltier devices; Power semiconductors; Temperature regulations; Active Thermal Control (ATC); Model Predictive Control (MPC); Peltier-device